PENGARUH TINGKAT KEMISKINAN TERHADAP PERTUMBUHAN EKONOMI DALAM PERSPEKTIF ISLAM - Angga Maulana; Muhammad Iqbal Fasa; Suharto Suharto (Jurnal Bina Bangsa Ekonomika, 2022)
Economic growth is a necessary condition for poverty reduction. The adequacy condition is that the growth is effective in reducing poverty. This study aims to determine the level of poverty that is affected by the COVID-19 pandemic which causes an increase in the poverty rate in Indonesia which affects the rate of economic growth. This research is a qualitative research with a descriptive approach method. With data collection techniques using library techniques or library research. Through research, it is hoped that the poverty rate can be reduced so that it affects the rate of economic growth with economic growth as an indication of the success of economic development